The secret life of another Indian nationalism: transitions from the Pax Britannica to the Pax Americana - Mayaram, Shail (Metamorphoses of the political: multidisciplinary approaches, 2022)
Introduction -- Colonialism, Orientalism, Nationalism and the Shaping of Popular -- History and Religion -- James Tod and Popular Indian Nationalism -- War and Violence in Savarkar's View of Indian History -- The Vishva Hindu Parishad's Fantasmagorical History -- The Politics of Vishva Hindu Parishad Conversion -- An Other history of Religion -- Myth and Medical Pluralism as Resistance to Hindu Nationalism.